A Systematic Review of Antimicrobial Stewardship Interventions in the Emergency Department. (September 2017) - Losier, Mia; Ramsey, Tasha D.; Wilby, Kyle John; Black, Emily K.
Background/Objective: To improve antimicrobial utilization, development and implementation of antimicrobial stewardship programs in the emergency department (ED) has been recommended. The primary objective of this review was to characterize antimicrobial stewardship (AMS) in the ED and to identify interventions that improve patient outcomes or process of care and/or reduce consequences of antimicrobial use.Methods: This study was completed as a systematic review. The following databases were searched from inception through November, 2016: MEDLINE, EMBASE, Cumulative Index to Nursing and Allied Health Literature, Scopus, and Web of Science. Randomized controlled trials, nonrandomized controlled trials, controlled and uncontrolled before-and-after studies, interrupted time series studies, and repeated-measures studies evaluating AMS interventions in the ED were included in the review. Studies published in languages other than English were excluded.Results: A total of 43 studies meeting inclusion criteria were identified from our search. Patient or provider education and guideline or clinical pathway implementation were the most commonly reported interventions. Few studies reported on audit and feedback, and no study evaluated preauthorization. Impact of interventions showed variable results. Where identified, benefits of AMS interventions primarily included improvement in delivery of care or a decrease in antimicrobial utilization; however, most studies were rated as having unclear or high risk of bias.Conclusion: AMS interventions in the ED may improve patient care. However, the optimal combination of interventions is unclear. Additional studies with more rigorous design evaluating core components of AMS programs, including prospective audit and feedback are needed.